2008
DOI: 10.1016/j.stem.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in the Niche Enforces Hematopoietic Stem Cell Quiescence and Is Necessary to Preserve Self-Renewal In Vivo

Abstract: Wingless (Wnt) is a potent morphogen demonstrated in multiple cell lineages to promote the expansion and maintenance of stem and progenitor cell populations. Wnt effects are highly context dependent, and varying effects of Wnt signaling on hematopoietic stem cells (HSCs) have been reported. We explored the impact of Wnt signaling in vivo, specifically in the context of the HSC niche by using an osteoblast-specific promoter driving expression of the paninhibitor of canonical Wnt signaling, Dickkopf1 (Dkk1). Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
404
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(421 citation statements)
references
References 56 publications
14
404
2
1
Order By: Relevance
“…Such discrepancies may in part be due to heterogeneity among cohorts of aged mice, or the sensitivity of different methods used to detect p16 Ink4a expression. Interestingly, Bondar and Medzhitov (2010) elegantly demonstrated that cell competition exists in regulated by a number of other BM niche-associated factors, including TPO, Wnt, and SDF-1 (Qian et al, 2007;Fleming et al, 2008;Nie et al, 2008). Collectively, these data indicate that multiple signaling mechanisms activated by developmental pathways and environmental factors may converge upon the regulation of CKI expression, which in turn might contribute to the prolonged passage of HSCs through the G 1 phase of the cell cycle.…”
Section: Cell-extrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 95%
See 1 more Smart Citation
“…Such discrepancies may in part be due to heterogeneity among cohorts of aged mice, or the sensitivity of different methods used to detect p16 Ink4a expression. Interestingly, Bondar and Medzhitov (2010) elegantly demonstrated that cell competition exists in regulated by a number of other BM niche-associated factors, including TPO, Wnt, and SDF-1 (Qian et al, 2007;Fleming et al, 2008;Nie et al, 2008). Collectively, these data indicate that multiple signaling mechanisms activated by developmental pathways and environmental factors may converge upon the regulation of CKI expression, which in turn might contribute to the prolonged passage of HSCs through the G 1 phase of the cell cycle.…”
Section: Cell-extrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 95%
“…Notably, TGF- and Notch ligands up-regulate CXCR4, and this may account for some of their quiescenceenforcing activity (Franitza et al, 2002). On the other hand, activation of the Wnt and Hh pathways is associated with increased expression of cyclin D1 in HSCs, although Wnt signaling is typically associated with maintenance of HSC quiescence and self-renewal activity (Fleming et al, 2008;Merchant et al, 2010). It may be that signaling through these pathways helps to maintain basal expression of cyclin D1 in quiescent HSCs (Passegué et al, 2005).…”
Section: Cell-extrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 99%
“…Nevertheless, several lines of evidence also indicate that β-catenin is dispensable for HSCs maintenance [16,17]. On the other hand, inhibition of environmental canonical Wnt signaling in osteoblasts impairs HSCs self-renewal and quiescence [18]. Collectively, canonical Wnt signaling is revealed to * These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…Wnt signaling is involved in HSC regulation (reviewed in [59,123]), and Wnt signaling was reported to maintain HSC in a quiescent status in vivo [124]. The effects of Wnt signaling are dosage and context dependent: low Wnt doses result in expansion of HSCs, whereas high doses cause exhaustion [125].…”
Section: Wnts and Glycogen Synthase Kinase 3 (Gsk-3) Inhibitormentioning
confidence: 99%